POLA SESAR SADDANG BERDASARKAN TINGKAT SEISMISITAS DAN FOKAL MEKANISME (Studi Kasus Januari 2010 - Juli 2020) - Risnawati Risnawati; Ihsan Ihsan; Ayusari Wahyuni; Muh. Said L. (JFT : Jurnal Fisika dan Terapannya, 2021)
The research of the Saddang fault pattern based on the level of seismicity and focal mechanism (a case study in January 2010- July 2020) aims to determine the level of seismicity in the Saddang fault area and the Saddang fault focal mechanism in the 2010-2020 earthquake. The data which were used were secondary data from the BMKG catalog from January 2010 - July 2020. The coordinating limit is 118.50 ° East Longitude 120.60 ° East Longitude and (-2.60 ° South Latitude) - (-5.70 ° South Latitude) there were 1425 earthquakes. This research used ArcGis application to measure seismicity distribution map and seiscomp3 to measure focal mechanism. Furthermore, the focal mechanism divides the region into three regions. The results which obtained from the seismicity map obtained a high level of seismicity with a shallow depth. Which was caused by the lack of factors from the active Saddang fault and Sulawesi who had four plate junctions. The results of the focal mechanism in each region had the whole type of shear fault or horizontal. Keywords: Earthquake, geology software ArcGis, software seisco